2022
DOI: 10.3390/ijms232214327
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Features of Liver Mitochondria and Mitophagy in Rats with Hyperthyroidism

Abstract: This work investigated the effect of thyroxine on the biogenesis and quality control system of rat liver mitochondria. Chronic administration of thyroxine to experimental animals induced hyperthyroidism, which was confirmed by a severalfold increase in serum-free triiodothyronine and thyroxine concentrations. The uptake of oxygen was found to increase with a decrease in ADP phosphorylation efficiency and respiratory state ratio. Electron microscopy showed 36% of liver mitochondria to be swollen and approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…It is the liver, unlike other organs, that is exposed to the strongest effects of the investigated substances during intraperitoneal administration. Thus, the results after the introduction of TH are likely to differ in the investigated animal organs, depending on the individual characteristics of the animal [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the liver, unlike other organs, that is exposed to the strongest effects of the investigated substances during intraperitoneal administration. Thus, the results after the introduction of TH are likely to differ in the investigated animal organs, depending on the individual characteristics of the animal [12].…”
Section: Discussionmentioning
confidence: 99%
“…Samples of the heart tissue for the transmission electron microscopy (TEM) imaging were taken from decapitated animals and fixed in a 2.5% glutaraldehyde solution in 0.1 M phosphate-buffered saline (PBS, pH 7.4) for 2-3 h [12]. The preparations were examined and photographed using a JEM-2000 FXII (JEOL Ltd., Tokyo, Japan).…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Radin, Muller and their collaborators have recently shown that stable two-layered lipid structures, resembling in their physical properties the lipid layers of natural membranes, can be reconstructed from crude extracts of brain lipids. A drop of brain lipid solution in a chloroform-methanol mixture [42] was placed in a narrow slit in a plastic partition between chambers containing a solution of KS1. As the solvents diffuse from the droplet into the aqueous phase, the oriented phospholipid molecules at the boundary of the two solvents in the droplet approach each other and eventually combine into a fairly stable double layer located across the gap.…”
Section: The Structure Of the Double Lipid Layermentioning
confidence: 99%
“…In this case, marked functional and structural changes occur in mitochondria. It is known that mitochondrial dysfunction plays an important role in both the development and progression of HT, especially due to the generation of oxidative stress, impaired oxidative phosphorylation, and improper operation of the system of mitochondrial quality control and mitophagy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%